TINDAK TUTUR ILOKUSI DALAM NASKAH DRAMA OBLADI OBLADA, TIGA NASKAH DRAMA TERPILIH KARYA DASRI AL-MUBARY - Hapidatul Hasanah; Auzar Auzar; Hasnah Faizah (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
ABSTRACTAbstract The form of illocutionary on the script of the drama “Obladi Oblada”, the threechoosen scripts of the drama worked by Dasri Al-Mubary, was identified the forms ofillocutionary such as assertive function that is assertive act of notifying, assertive function ofdeclaring, assertive function of complaining, assertive function of demanding, assertivefunction of informing, assertive function of proposing. Thereafter, the forms of directiveillocutionary found are directive act of ordering, directive act of commanding, directive act ofquestioning, directive act of requesting, directive act of asking, directive act of suggesting,directive act of advicing, directive act of prohibiting, and directive act of threatening. Amongthose all illocutionary forms identified, there is a prominent illocutionary form that isillocutionary act of directive. The form of illocutionary act of directive is the most frequent inappearance, and what is more is there is also the the first functions of illocutionary actidentified, that is the function of competitive illocutionary act which indicates that the goalsof the illocution competes with the goals of social, the second one is that the fucntion ofconvival illocutionary act in which the goals of illocution are in line with the goals of thesocial, the third is the function of collaborative illocutionary act in which its goals have noeffect toward the goals of the social, and the last one is the function of conflictiveillocutionary act in which its illocutionary goals oppose against the social goals.Keyword: illocutionary act, Obladi Oblada Drama